Thoracic Paravertebral Block for Postoperative Analgesia in Pediatric Oncology - E. I. Belousova; N. V. Matinyan; Z. S. Ordukhanyan (Общая реаниматология)
Objective: to enhance the efficiency and safety of anesthesia during thoracic surgical interventions in pediatric cancer surgery, by using general anesthesia in combination with thoracic paravertebral analgesia.Subjects and methods. A prospective, randomized trial was conducted. Intra- and postoperative data were analyzed in 90 patients who had been operated on for lung and thoracic malignancies. There were two patient groups: 1) 50 children who used continuous thoracic paravertebral block (PVB) with ropivacaine 0.3% as part of combined balanced anesthesia and 2) 40 children who received epidural block with ropivacaine 0.2% as an analgesic component of combined anesthesia. All the patients underwent hemodynamic monitoring; postoperative pain assessment were carried out by a visual analogue scale (VAS) in children above 3 years of age and by the modified Douleur Aigue du Nouveau-ne (DAN) scale in those below the age of 3 years.Results. The trial has demonstrated that the analgesic effect during continuous PVB in the intra- and postoperative periods is comparable with that of epidural block with ropivacaine 0.2%; however, it has a higher hemodynamic stability. Ultrasound guided PVB has sufficient safety. The postoperative complications were  pneumonia  in  2  (4%)  patients  in  the  PVB  group;  these  were  associated  with  the  baseline  patient  status  in  5 (12.5%) children in the epidural analgesia group. Postoperative nausea was found in only 6% of the patients in the PVB group.Conclusion. The proposed modification of ropivacaine 0.3% injection into the paravertebral space under ultrasound guidance can increase the extent of the local anesthetic, thus enhancing the efficiency of PVB. The efficiency of the block is 98.1% versus 86% of the given by foreign authors.